Summary of the chosen methodologies and practices to produce GHGE-estimates for an average European diet - Hartikaiinen, Hanna; Pulkkinen, Hannele (Natural Resources Institute Finland, Luke, 2016)
The primary goal of our study was to produce greenhouse gas emission -estimates (GHGE-estimates) for average diets in Europe to be used in SUSDIET-project (Towards Sustainable Diets in Europe, the ERANET SUSFOOD Call 2014–2017). The SUSDIET-project aim was to optimize diets from environ-mental and nutritional point of view and to evaluate impacts of information policies of promoting sustainable diets. We used a categorization of 151 food categories and gave GHGE-estimates for each food category. Altogether, we used 80 indicator products to represent the 151 food categories. GHGE-estimates of food product categories were based on statistics and existing literature (LCA-based studies) where we included agricultural production – and processing steps. We went through numerous studies (mostly scientific, peer reviewed articles) and chose literature-references with similar methodologies. We used literature- and expert evaluation -based GHGE-defaults for cooking, storing and packing, and left transportation and consumers’ travels to grocery stores outside our system boundaries. Additionally, since the used dietary data was based on food consumed (daily food consumption data reported by participating consumers from UK, France, Italy, Finland and Sweden), we used conversion factors to convert the GHGE-estimates of produced food to match the weight of food consumed. As uncertainties of the GHGE-estimates are high, uncertainty ranges for the GHGE-estimates of the 151 food categories were also produced.
Keywords: climate impact; diet; harmonization; uncertainty